Production methods and analysis of cotton waste bio-gas to reduce environmental pollution - SENDILVELAN.S; SUNDARRAJ.C; BHASKAR.K (International Journal of Pharma and Bio Sciences, 2017)
In this work an attempt has been made to generate methane from cotton waste by considering the problem of cotton waste from textile industries. Experiments were conducted with different proportion of water, and with or without addition of seeding materials. The bio gas production was optimized for maximum yield with high percentage of methane with respect to the percentage of different seeding material and working temperature. Using micro-organisms, it is possible to achieve a higher yield of enzymes, and to genetically manipulate the production with desired properties for the conversion of natural fats and oils into biodiesel. It was found that cotton waste with 10% seeding material like cow dung or pig dung at the temperature level of 30ºC are generating bio gas continuously after ten days of feeding with reasonably high yield value. The gas generated in this method was tested in gas chromatography and found that it contains 79% methane rather than 60% methane in other techniques, and hence it has high calorific value.